Afkolonisering, boliger og kvindeforeninger i Grønland ca. 1945 til 1970 - Rud, Søren (Historisk Tidsskrift, 2023)
Decolonization, Housing and Women’s Associations in Greenland, c. 1945-1970 Housing was one of the most fundamental areas of change in Greenland after World War 2. Politicians, experts, and officials established programs aimed at nothing less than replacing all Greenlandic housing facilities. When Greenlandic women’s associations began to engage with the issue in the mid-1960s, housing also became an important mobilization point for Greenlandic civil society. This article shows, firstly, that the high modernist ideas of efficient and rational planning of housing and social life in Greenland did not take hold until the 1960s, when multi-storey housing gradually became dominant. Secondly, in addition to the aim of improving health and living conditions in the country, housing planners operated on the assumption that the new housing could facilitate Greenlanders’ adaption to ’modern life’. Housing was thus a key reform tool. Finally, the analysis shows that housing projects had a far-reaching effect on Greenlandic society in terms of mobilization. The debate raised by the women’s associations shows different attitudes and desires in relation to housing and lifestyles. On the one hand, many wanted modern housing with up-to-date facilities. On the other hand, they wanted influence on the development and for the housing to be adapted to a Greenlandic context.